Perempuan Bumi: Diferensiasi Ketubuhan pada Laki-Laki dan Perempuan dalam Wahana Feminisme - Lara Aprilia; Wahyu Trisno Aji (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
The differentiation of sexes between men and women becomes a complex subject, involving biological, psychological, and social factors. Physical differences, including body structure, reproductive organs, and hormones, serve as primary distinctions between them. Psychologically, patterns of thought, emotions, and responses to the environment also differ between men and women. On the social front, norms and gender stereotypes shape societal perceptions of gender roles and identities. While these differences exist, it is important not to narrow individuals into gender stereotypes and to recognize individual diversity. A deeper understanding of sexual differentiation helps create an inclusive environment for all individuals, without discrimination based on gender.